2014
DOI: 10.3892/mco.2014.338
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic interactions of the anti-casein kinase 2 CIGB-300 peptide and chemotherapeutic agents in lung and cervical preclinical cancer models

Abstract: Abstract. CIGB-300 is a novel clinical-stage synthetic peptide that impairs the casein kinase 2 (CK2)-mediated phosphorylation of B23/nucleophosmin in different experimental settings and cancer models. As a single agent, CIGB-300 induces apoptosis in vitro and in vivo and modulates an array of proteins that are mainly involved in drug resistance, cell proliferation and apoptosis, as determined by proteomic analysis. However, the clinical oncology practice and cumulative knowledge on tumor biology suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…(37). Other in vitro investigations, using combinations of CIGB-300 with chemotherapeutic agents including paclitaxel, doxorubicin, cisplatin, and 5-fluorouracil in lung and cervical cancer cell models, show promise for further clinical investigation (38). Paclitaxel displayed the strongest synergism with CIGB-300 in NCI-H125 and SiHa cell lines, with 5-fold less peptide being required to achieve an antiproliferative effect level of 94% in NCI-H125 cells.…”
Section: Cigb-300: a Csnk2 Inhibitory Peptide In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…(37). Other in vitro investigations, using combinations of CIGB-300 with chemotherapeutic agents including paclitaxel, doxorubicin, cisplatin, and 5-fluorouracil in lung and cervical cancer cell models, show promise for further clinical investigation (38). Paclitaxel displayed the strongest synergism with CIGB-300 in NCI-H125 and SiHa cell lines, with 5-fold less peptide being required to achieve an antiproliferative effect level of 94% in NCI-H125 cells.…”
Section: Cigb-300: a Csnk2 Inhibitory Peptide In Clinical Trialsmentioning
confidence: 99%
“…Paclitaxel displayed the strongest synergism with CIGB-300 in NCI-H125 and SiHa cell lines, with 5-fold less peptide being required to achieve an antiproliferative effect level of 94% in NCI-H125 cells. With the same combination setting, the concentration of paclitaxel could be reduced more than 3,000-fold without compromising the final antiproliferative effect (38). Ongoing trials for optimization of CIGB-300 treatment and delivery approaches highlight its utility as an alternative to small-molecule ATP-competitive inhibitors for targeting CSNK2 in cancer (39).…”
Section: Cigb-300: a Csnk2 Inhibitory Peptide In Clinical Trialsmentioning
confidence: 99%
“…CIGB-300 exerts a broad antiproliferative effect on cell lines derived from breast, cervical, lung, colon, prostate cancer and chronic lymphocytic leukemia (CLL) while a robust antitumour effect was also observed in vivo in mouse models of cervical and lung cancer as well as CLL [98, 103, 104]. Recently it was also observed that the concomitant administration of CIGB-300 and drugs like cisplatin, paclitaxel, doxorubicin or 5-fluorouracil cisplatin gives rise to synergic chemotherapeutic effects in lung and cervical cancer models [105]. …”
Section: Cigb-300mentioning
confidence: 99%
“…Lung cancer is a highly malignant disease and the incidence is increasing annually (1). With the enhancement and popularity of efforts aimed at educating individuals about not smoking, this incidence rate of smoking has shown a declining trend.…”
Section: Introductionmentioning
confidence: 99%
“…Foxp3 transforms primary CD4 + T cells into CD4 + regulatory T cells, and the normal expression of the gene is built around the premise that CD4 + regulatory T cells play a role (6). The Janus kinase 2/signal transducer and activator of transcription 4 (JAK2/STAT4) signaling pathway is activated continuously and abnormally activated in a variety of tumor tissues and cell lines, which promotes tumor growth, invasion, angiogenesis and metastasis (1). Increased activation of the the JAK2/STAT4 signaling pathway has been demonstrated in a variety of tumors, including stomach and liver cancer (2).…”
Section: Introductionmentioning
confidence: 99%